Material innovation: case studies of tangible working material in technology, art and design - Berg, Arild; Rodrigues, Osmar Vicente [UNESP]; Haugen, Sigrid; Puhkan, Urmas; Stoltenberg, Einar; Wettre, Mikkel; Boks, C.; Sigurjonsson, J.; Steinert, M.; Vis, C.; Wulvik, A. (Design Soc, 2016)
There are still unexplored entrepreneurial potentials for collaboration in design, art and engineering. Heimdal and Rosenquist explored three roles of textiles as tangible working materials in such co-design processes. However, more knowledge of innovative design processes that involve new use of materials is needed. The aim of this study was to identify potentials for sustainable innovation in tangible working materials in design processes. This was analysed in a 'preservation of diverse cultures' perspective from Deep Ecology. Case studies were performed on the design and engineering of innovative use of materials for product development and design of the environment. Contexts for the case studies included cement industries, experimental use of cement in design education, 3D printing of plaster-based, clay-based and cement-based composites, public art in a terrazzo floor in a school and concrete art sculptures in a hospital park. The findings were discussed in relation to ecology to contribute to concepts for sustainable collaborative practices between technology, art and design.
Keywords: artistic research; participatory design; Deep Ecology; chemical products